“Visions of the Possible”: Collaborative-Interdisciplinary Approaches to Teaching and Learning - Cusack-McVeigh, Holly; Wilson, Mark (Teaching and Learning Inquiry, 2025)
In this article we explore the challenges and rewards of a multi-year, multi-disciplinary, multi-institutional approach to collaborative teaching and learning. What does it mean to teach across disciplines and what might this look like for our students who are emerging professionals from very different fields of study? What are the challenges of adopting a collaborative model for teaching and learning? How might we envision new instructional approaches that positively impact student learning and success while simultaneously addressing the needs of our community partners? What new pedagogical approaches are emerging that might address challenges within higher education? Our inquiry here is focused on what might be if we make the time to explore new ways of teaching both in and out of the classroom. Following Hutchings’ (2000) call for “visions of the possible” in higher education, we present three distinct case studies that demonstrate the potential of deeply engaged, collaborative teaching and learning across disciplines. We ask what this experimental approach might mean for future educators and students alike.